Ductal carcinoma in situ: a challenging disease - Sevilay Altintas; Manon T. Huizing; Eric Van Marck; Jan B. Vermorken; Wiebren A. Tjalma (Frontiers Media S.A., 2011)
Ductal carcinoma in situ (DCIS) represents a heterogenous group of lesions with variable malignant potential. Although it is clearly pre-invasive, not all lesions progress to an invasive malignant disease. The significant increase in the frequency of diagnosis is the result of both widespread use of screening mammography and better recognition among pathologists. Treatment is controversial, but for several decades total mastectomy has been considered as the appropriate treatment. The tendency to be less aggressive in terms of surgery has followed the pattern of events observed in the treatment of invasive breast carcinomas. More recently, it has become clear that breastconserving procedures could be applied and selected on the basis of diagnostics and risk factors. When all patients with DCIS are considered, the overall mortality is extremely low, only about 1-2%. On the other hand, breast-conserving surgery is only curative in 75-85%; 50% of the local recurrences have proven to be invasive with a mortality rate of 12-15%. There is no place for axillary node dissection, adjuvant hormonal treatment or chemotherapy in the treatment. Important factors in predicting local recurrence are age, family history, nuclear grade, comedo-type necrosis, tumor size and margin width. With the addition of radiation therapy to excisional surgery, there is a 50% reduction in the overall local recurrence rate. The Van Nuys Prognostic Index (VNPI), recently updated, is a tool that quantifies measurable prognostic factors that can be used in the decision-making process of treatment. Recent data from large cohort studies and randomized trials have emerged to guide treatment. DCIS is now understood to have diverse malignant potential and it is unlikely that there will be a single treatment for this wide range of lesions. Advances in molecular biology and gene expression profiling of human breast tumors have been providing important insights into the relationship between DCIS and invasive breast cancer.